2014
DOI: 10.1098/rspb.2013.3320
|View full text |Cite
|
Sign up to set email alerts
|

Why fruit rots: theoretical support for Janzen's theory of microbe–macrobe competition

Abstract: We present a formal model of Janzen's influential theory that competition for resources between microbes and vertebrates causes microbes to be selected to make these resources unpalatable to vertebrates. That is, fruit rots, seeds mould and meat spoils, in part, because microbes gain a selective advantage if they can alter the properties of these resources to avoid losing the resources to vertebrate consumers. A previous model had failed to find circumstances in which such a costly spoilage trait could flouris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Janzen 11 suggested that fruits infested by microbes are rarely eaten by vertebrates because microbes produce toxic compounds and reduce the nutritional value of infested fruit. Most empirical investigations of these cross-kingdom interactions 1214 as well as recent theoretical evidence have supported Janzen’s famous prediction 15 , but see 16 . Nonetheless, there exist a handful of studies showing that frugivores prefer infested fruits 9, 17–19 .…”
Section: Introductionmentioning
confidence: 89%
“…Janzen 11 suggested that fruits infested by microbes are rarely eaten by vertebrates because microbes produce toxic compounds and reduce the nutritional value of infested fruit. Most empirical investigations of these cross-kingdom interactions 1214 as well as recent theoretical evidence have supported Janzen’s famous prediction 15 , but see 16 . Nonetheless, there exist a handful of studies showing that frugivores prefer infested fruits 9, 17–19 .…”
Section: Introductionmentioning
confidence: 89%
“…This process occurs when fruit becomes infected by yeasts capable of producing ethanol via fermentation under anaerobic conditions (Levey, 2004). Ethanol production by yeasts increases their competiveness, as ethanol may deter frugivorous competitors (Dudley, 2004;Janzen, 1977;Ruxton et al, 2014). However, the negative relationship between sugar and ethanol content in fruit is quite weak, presumably because over-ripe or rotting fruit constitutes a heterogeneous milieu for micro-organisms.…”
Section: Introductionmentioning
confidence: 99%
“…() suggested that d ‐limonene was present in wild‐type orange fruit to promote infection by microorganisms that facilitated access to the fruit pulp by frugivores and thus aided seed dispersal. However, many vertebrates, including humans, are very sensitive to microbial spoilage of potential foods and find such spoilage highly aversive (Ruxton et al ., ). In this case, spoilt fruit might act to deter specific frugivores but attract others.…”
Section: Discussionmentioning
confidence: 97%